2012
DOI: 10.1021/nl204420s
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Plasmonics of Metallic Nanostructures

Abstract: The requirements for spatial and temporal manipulation of electromagnetic fields on the nanoscale have recently resulted in an ever-increasing use of plasmonics for achieving various functionalities with superior performance to those available from conventional photonics. For these applications, ohmic losses resulting from free-electron scattering in the metal is one major limitation for the performance of plasmonic structures. In the low-frequency regime, ohmic losses can be reduced at low temperatures. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
100
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(109 citation statements)
references
References 27 publications
9
100
0
Order By: Relevance
“…In this paper, we present experimental results on the temperature dependence of the SP resonance energy and width in copper nanoparticles 17-59 nm in size embedded in the silica matrix in the temperature interval 293-460 K. We have observed that an increase of the temperature of a sample leads to the red shift and the broadening of the SP resonance, which is similar to our results [36] obtained for Ag nanoparticles in silica at high temperatures and to results of Bouillard et al [33] obtained for Au nanostructures at low temperatures. We analyze the observed temperature dependence of the SP resonance within the framework of a theoretical model considering such phenomena as the thermal volume expansion of a nanoparticle, electron-phonon scattering in a nanoparticle, and temperature dependence of the dielectric permittivity of the host matrix.…”
Section: Introductionsupporting
confidence: 89%
“…In this paper, we present experimental results on the temperature dependence of the SP resonance energy and width in copper nanoparticles 17-59 nm in size embedded in the silica matrix in the temperature interval 293-460 K. We have observed that an increase of the temperature of a sample leads to the red shift and the broadening of the SP resonance, which is similar to our results [36] obtained for Ag nanoparticles in silica at high temperatures and to results of Bouillard et al [33] obtained for Au nanostructures at low temperatures. We analyze the observed temperature dependence of the SP resonance within the framework of a theoretical model considering such phenomena as the thermal volume expansion of a nanoparticle, electron-phonon scattering in a nanoparticle, and temperature dependence of the dielectric permittivity of the host matrix.…”
Section: Introductionsupporting
confidence: 89%
“…To explain this result, it is important to note that we have neglected the influence of the temperature on the Au rings themselves in the discussion. As documented in a few studies, the plasmonic properties of nanoparticles with significant surface roughness such as our lithographied rings are only marginally affected by the temperature, except for a slight narrowing and blue shifting of the peak as T decreases [38]. This is such a spectral evolution that we observe in Fig.…”
supporting
confidence: 83%
“…More recently, there have been reports on the temperature dependent optical constants of 200-nm-thick silver films [16][17][18] as well as the temperature changes in the surface plasmon resonance of gold nanoparticles embedded in silica at elevated temperatures 19 . At low temperatures, optical properties of ultrathin Au films in the mid-and far-infrared regions 20 and the optical response of gold nanorods and plasmonic crystals 21 have also been studied. However, a comprehensive study of the optical properties of gold thin films with varying thicknesses over a wide wavelength range at elevated temperatures has not been conducted.…”
Section: Abstract: Nanophotonics Plasmonics Metamaterials Metal Opmentioning
confidence: 99%